Metabolismo oxidativo sérico em ratos diabéticos com lesão periapical - Prieto, Annelise Katrine Carrara [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This study aimed to evaluate the influence of endodontic infection associated with or without diabetes, in the serum concentrations of endogenous antioxidants albumin, bilirubin and uric acid, total antioxidant capacity (TAC) and oxidant parameter, malondialdehyde (MDA) in blood serum of the Wistar. It were used 40 rats in 4 groups: euglycemic (E); euglycemic with periapical lesion (PL); diabetic (D) and diabetic with periapical lesion (D + PL). Diabetes was chemically induced by alloxan intramuscularly at a dose of 150 mg/kg and periapical lesion by exposure right first molar to the oral environment for 30 days. After this period, blood was collected via cardiac puncture to obtain serum, and also the hemi-jaws for histological processing. Albumin measurement by bromocresol green technique, bilirubin by Van der Bergh, uric acid by uricase, TAC by capturing the free radical ABTS, and MDA by assay of thiobarbituric acid reactive substances (TBARS) were performed in serum. In the histological analysis, the intensity and extent of inflammation, root resorption and bone loss were evaluated. The values were analyzed by analysis of variance tests (ANOVA) and Tukey‟s test (p < 0.05). The values obtained for scores were statistically analyzed by the Kruskal- Wallis test and Dunn‟s tests (p < 0.05). In diabetic rats (D and D + PL) there was an increase in the concentration of MDA and uric acid while decrease in albumin compared to euglycemic rats (E and PL). D + PL group compared to D showed an increase of uric acid and decreased albumin. Histological analysis showed periapical lesion of diabetic rats (D + PL) has a greater severity when compared with the euglycemic rats (PL). Periapical lesion associated with diabetes changes the antioxidant status, reducing serum levels of albumin and increasing serum levels of uric acid

Este trabalho teve como objetivo avaliar a influência da infecção endodôntica associada ou não à diabetes, nas concentrações séricas dos antioxidantes endógenos albumina, bilirrubina e ácido úrico, da capacidade antioxidante total (TAC) e do parâmetro oxidante malonaldeído (MDA) em soro sanguíneo de ratos Wistar. Foram utilizados 40 ratos divididos em 4 grupos: euglicêmicos (C); euglicêmicos com lesão periapical (LP); diabético (D) e diabético com lesão periapical (D+LP). A diabetes foi induzida quimicamente pela utilização da droga Aloxano, via intramuscular, na dose de 150 mg/kg, e a lesão periapical, por meio da exposição pulpar do primeiro molar superior direito ao meio bucal durante 30 dias. Após este período, foi coletado o sangue, através de punção cardíaca para obtenção do soro, e também, as hemimaxilas, para o processamento histológico. No soro foi realizada a mensuração da albumina pela técnica verde de bromocresol, bilirrubina por Van der Bergh, ácido úrico pela uricase, TAC pela captura do radical livre ABTS, e MDA pelo ensaio das substâncias reativas ao ácido tiobarbitúrico (TBARS). Na análise histológica foram avaliadas a intensidade e extensão da inflamação, reabsorção radicular e tamanho da lesão. Os valores foram analisados pelos testes de análise de variância (ANOVA) e de Tukey (p<0,05). Os valores obtidos em escores foram analisados estatisticamente, por meio dos testes de Kruskal-Wallis e Dunn (p<0,05). Nos ratos diabéticos (D e D+LP) houve um aumento da concentração de MDA e ácido úrico e uma diminuição de albumina em relação aos ratos euglicêmicos (C e LP). O grupo D+LP comparado ao D apresentou um aumento de ácido úrico e diminuição de albumina. A análise histológica mostrou que a lesão periapical de ratos diabéticos (D+LP) possui maior severidade quando comparada com a dos ratos euglicêmicos (LP). A lesão...
Keywords: Diabetes; Stress oxidativo; Endodontia